BALE KULKUL DI BARAT DAYA CATUS PATA PURI PEMECUTAN DI DENPASAR - Bagus Arjana Wira Putra, I Ketut (Humanis; Volume 1. No. 1. November 2012)
“Bale Kulkul” in southwest of catus pata Puri Pemecutan in Denpasar is a part of Pura Dalem Tambangan Badung which is interpreted that established in the similar time with the establish of Puri Pemecutan in the early 19th. This research purpose was conducted to recognize the design, function, and meaning which are contained in the “Bale Kulkul” building, the heritage of Badung Palace. According to the research purpose, the type of research that used is qualitative. The steps of research consist of the collect, processing, and analyze of data. The analyses that used are function analysis, figure analysis, morphology analysis, and style analysis. The research result which recognized that the bale kulkul design in southwest of catus pata Puri Pemecutan in Denpasar has the form square, and divided into three parts, that are: batis/foot, pengawak/body, duwur/head part. This building is combined with Balinese style, Netherland style, and China style. The functions are as the information tools for the inhabitant or follower “penyungsung”, and for the religious ceremony in Pura Dalem Tambangan Badung. Bale Kulkul building has the meaning for Pura Dalem Tambangan Badung, Puri Pemecutan Denpasar, for catus pata in Puri Pemecutan Denpasar, for inhabitant/follower Pura Dalem Tambangan Badung, for Denpasar city, and also has the meaning for the variety of ornament that used on the bale kulkul building which stand u straight on the Imam Bonjol street, Denpasar.